2016
DOI: 10.1073/pnas.1521036113
|View full text |Cite
|
Sign up to set email alerts
|

Transition state for the NSD2-catalyzed methylation of histone H3 lysine 36

Abstract: Nuclear receptor SET domain containing protein 2 (NSD2) catalyzes the methylation of histone H3 lysine 36 (H3K36). It is a determinant in Wolf-Hirschhorn syndrome and is overexpressed in human multiple myeloma. Despite the relevance of NSD2 to cancer, there are no potent, selective inhibitors of this enzyme reported. Here, a combination of kinetic isotope effect measurements and quantum chemical modeling was used to provide subangstrom details of the transition state structure for NSD2 enzymatic activity. Kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
80
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(90 citation statements)
references
References 58 publications
10
80
0
Order By: Relevance
“…This primary methyl - 14 C KIE is consistent with values reported for NSD2, 14 DNMT1, 15 and glycine N -methyltransferase (GNMT). 21 The large magnitude of this KIE indicates that methyl transfer for hPNMT proceeds via a rate-limiting S N 2 mechanism.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…This primary methyl - 14 C KIE is consistent with values reported for NSD2, 14 DNMT1, 15 and glycine N -methyltransferase (GNMT). 21 The large magnitude of this KIE indicates that methyl transfer for hPNMT proceeds via a rate-limiting S N 2 mechanism.…”
supporting
confidence: 89%
“…22 These isotope effects are in agreement with previous studies that support methyl transfer as the rate-limiting step of the PNMT reaction. 9,10 DFT calculations for NSD2 14 and DNMT1 15 suggest that the primary 36 S KIE on methyltransferase reactions is proportional to the loss of bond order between the carbon of the transferring methyl (C Me ) and the sulfur of SAM at the TS. The 36 S KIE for hPNMT (1.014 ± 0.005) is smaller than those measured for NSD2 (1.018 ± 0.008) 14 and DNMT1 (1.019 ± 0.006), 15 suggesting that hPNMT TS structure may retain somewhat greater C Me –S bond order.…”
mentioning
confidence: 99%
“…Our experimental KIEs and BIEs revealed that the SET8-catalyzed methylation goes through an early, asymmetrical S N 2 TS with the long N-C distance of 2.35-2.40 Å and the short S-C distance of 2.00-2.05 Å. Poulin et al (59) recently reported KIEs of NSD2 and solved its TS structure. In comparison with the early S N 2 TS of SET8, the TS structure of NSD2 shows the later, asymmetrical S N 2 characters with a short N-C distance of 2.02-2.10 Å and a long S-C distance of 2.5 Å.…”
Section: Computational Modeling Of Transition State Of Set8-catalyzedsupporting
confidence: 52%
“…Similar to NSD1, the NSD2 post-SET domain is attached to the catalytic SET domain via an autoinhibitory loop region and inhibition is relieved upon nucleosome binding (Qiao et al 2011; Poulin et al 2016a). Furthermore, NSD2 has been reported to preferentially catalyze H3K36 dimethylation compared to H3K36 monomethylation (Li et al 2009b; Kuo et al 2011; Poulin et al 2016b). …”
Section: Identification and Function Of Nsd2mentioning
confidence: 99%